A framework of place branding, place image, and place reputation: Antecedents and moderators. Issue 2 (11th April 2016) - Foroudi, Pantea; Gupta, Suraksha; Kitchen, Philip; Foroudi, Mohammad M.; Nguyen, Bang
Abstract : Purpose: This paper aims to develop a framework that links the concepts of place branding, place image and place reputation. Focusing on the antecedents and outcomes of place branding in the context of an emerging country, namely, Iran, the model further examines critical moderation variables. Design/methodology/approach: A qualitative approach was undertaken, comprising face-to-face in-depth interviews with 15 respondents, involved in communicating about their country for various purposes such as encouraging tourism, promoting exports and attracting investments. Based on analysis of the qualitative data, a comprehensive framework for place branding was formulated. Findings: Findings indicate that the key indicators of identifying a place brand come under two headings, namely, national culture (country's name, country's brand, country attributes, social changes, geography and environment, people, culture (history, language, etc.) and infrastructure (security, economic condition, technological advancement, tourism development goals, place marketing and promotional strategy), which influences on the favorability of place branding. In addition, five main moderators of the outcomes of place branding were identified, namely, political perception, social media and news, place awareness, place association and tourism experience. Practical implications: Effective place branding could help a country attract tourists, visitors, traders and investors. Place branding should be considered a constructive tool that can be successfully applied to managing a country's image. Originality/value: Place branding has received little attention in the context of emerging markets. This is the first known study undertaken with a view to understand and develop a place branding model that links with place image and place reputation in an emerging country. The study identifies 12 antecedents of place branding and five important moderators. Findings will help policymakers, country brand managers and communication professionals more generally who deal with a country's image and reputation and those involved in improving the tourism industry in Iran.